Melatonin as a Multipotent Component of Fish Feed: Basic Information for Its Potential Application in Aquaculture - Acharyya, Akash; Das, Joydeep; Hasan, Kazi Nurul (Frontiers in Marine Science, 2021)
In vertebrates, melatonin (N-acetyl-5-methoxy-tryptamine, MEL) is synthesized from L-tryptophan (L-Trp), primarily in the pineal gland and additionally in several non-pineal tissues, including enterochromaffin cells of the gastrointestinal tract. The biosynthesis of MEL in the pinealocytes exhibits a daily rhythm with a nocturnal peak in synchronization with the dark phase of an environment. However, the temporal pattern of the gut melatoninergic system in fish is known to be synchronized with one or more non-photic external cue(s), of which most notable include the components of food and feeding time in a daily cycle. Experimental findings on the use of L-Trp (5-fold to −8-fold higher with respect to standard) as a fish food supplement suggest that it has a stimulatory influence on gut MEL synthesis that ultimately leads to elevated levels of plasma MEL. Several studies employing MEL as a fish feed additive report variable responses in relation to the physiological functions of the fish and its doses of application and modes of exposure. Oral administration of MEL (validated dose in general: 200 mg/kg fish food) causes an increase in gut MEL concentrations, food intake capacity, and micronutrient selection ability of fish, as well as enhanced activity of antioxidative enzymes and/or reduced levels of biological stress markers like plasma cortisol and lactate. The application of MEL with the doses of 50 and 250 mg/kg fish food to balanced diet results in precious maturation of gonads, high live sperm rate, and good quality seeds in catfish. A few studies on different fish groups administered with MEL through tank water reveal a significant increase in the fecundity rate, percentage of fertilization, and the number of hatched embryos. MEL injection through intraperitoneal or intramuscular routes also elicits variable responses in fish. Several studies suggest a major protective role of endogenous MEL against gastric ulcer induced by pathogenic bacterial infection. Taken together, MEL seems to be a multipotent physiological candidate involved in the regulation of a variety of body functions ranging from the synchronization of vital activities with environmental variables to the timing of reproduction in a changing system, from the acceleration of body growth to the determination of a pattern of development, and from the reduction of oxidative stress to the protection against microbial infections. Because aquaculture aims at substantially improving the quality and quantity of available aquatic resources employing convenient, consistent, and commercially exploitable measures, we find the reasons to suggest that the use of MEL or its precursor L-Trp as a fish food supplement may open up a new vista of aquaculture and, hence, present this review with an attempt to present the basic information on this area of interest to justify the hypothesis.